Oncocytic Papillary Thyroid Carcinoma and Oncocytic Poorly Differentiated Thyroid Carcinoma: Clinical Features, Uptake, and Response to Radioactive Iodine Therapy, and Outcome - Lukovic, Jelena; Petrovic, Irina; Liu, Zijin; Armstrong, Susan M.; Brierley, James D.; Tsang, Richard; Pasternak, Jesse D.; Gomez-Hernandez, Karen; Liu, Amy; Asa, Sylvia L.; Mete, Ozgur (Frontiers in Endocrinology, 2021)
Objective The main objective of this study was to review the clinicopathologic characteristics and outcome of patients with oncocytic papillary thyroid carcinoma (PTC) and oncocytic poorly differentiated thyroid carcinoma (PDTC). The secondary objective was to evaluate the prevalence and outcomes of RAI use in this population. Methods Patients with oncocytic PTC and PDTC who were treated at a quaternary cancer centre between 2002 and 2017 were retrospectively identified from an institutional database. All patients had an expert pathology review to ensure consistent reporting and definition. The cumulative incidence function was used to analyse locoregional failure (LRF) and distant metastasis (DM) rates. Univariable analysis (UVA) was used to assess clinical predictors of outcome. Results In total, 263 patients were included (PTC [n=218], PDTC [n=45]) with a median follow up of 4.4 years (range: 0 = 26.7 years). Patients with oncocytic PTC had a 5/10-year incidence of LRF and DM, respectively, of 2.7%/5.6% and 3.4%/4.5%. On UVA, there was an increased risk of DM in PTC tumors with widely invasive growth (HR 17.1; p<0.001), extra-thyroidal extension (HR 24.95; p<0.001), angioinvasion (HR 32.58; p=0.002), focal dedifferentiation (HR 19.57, p<0.001), and focal hobnail cell change (HR 8.67, p=0.042). There was additionally an increased risk of DM seen in male PTC patients (HR 5.5, p=0.03).The use of RAI was more common in patients with larger tumors, angioinvasion, and widely invasive disease. RAI was also used in the management of DM and 43% of patients with oncocytic PTC had RAI-avid metastatic disease. Patients with oncocytic PDTC had a higher rate of 5/10-year incidence of LRF and DM (21.4%/45.4%; 11.4%/40.4%, respectively). Patients with extra-thyroidal extension had an increased risk of DM (HR 5.52, p=0.023) as did those with angioinvasion. Of the patients with oncocytic PDTC who received RAI for the treatment of DM, 40% had RAI-avid disease. Conclusion We present a large homogenous cohort of patients with oncocytic PTC and PDTC, with consistent pathologic reporting and definition. Patients with oncocytic PTC have excellent clinical outcomes and similar risk factors for recurrence as their non-oncocytic counterparts (angioinvasion, large tumor size, extra-thyroidal extension, and focal dedifferentiation). Compared with oncocytic PTCs, the adverse biology of oncocytic PDTCs is supported with increased frequency of DM and lower uptake of RAI.